2015
DOI: 10.1007/s00300-015-1678-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and mesozooplankton responses during two contrasting summers in a coastal Antarctic environment

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag Berlin Heidelberg. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
(76 reference statements)
3
17
0
Order By: Relevance
“…Field experiments indicate that viral lysis of phytoplankton (both picoplankton and nanoplankton) can be relatively minor in the WG, while grazing by microzooplankton exerts significant control of phytoplankton growth (Agustí & Duarte, ; Evans & Brussaard, ; Froneman & Perissinotto, ; Henjes et al, ; Jacobsen et al, ). In contrast, larger zooplankton are of secondary relevance in controlling phytoplankton biomass (Garcia et al, ). Although the grazing impact of both krill and salps on phytoplankton is moderate through most of the Southern Ocean, it should be noted that salps can in some instances control bloom formation (Perissinotto & Pakhomov, ) and that the impact of krill grazing may be underestimated due to the difficulty of measuring krill abundance and distribution (Smetacek et al, ).…”
Section: Biology I: Phytoplankton Of the Wgmentioning
confidence: 99%
“…Field experiments indicate that viral lysis of phytoplankton (both picoplankton and nanoplankton) can be relatively minor in the WG, while grazing by microzooplankton exerts significant control of phytoplankton growth (Agustí & Duarte, ; Evans & Brussaard, ; Froneman & Perissinotto, ; Henjes et al, ; Jacobsen et al, ). In contrast, larger zooplankton are of secondary relevance in controlling phytoplankton biomass (Garcia et al, ). Although the grazing impact of both krill and salps on phytoplankton is moderate through most of the Southern Ocean, it should be noted that salps can in some instances control bloom formation (Perissinotto & Pakhomov, ) and that the impact of krill grazing may be underestimated due to the difficulty of measuring krill abundance and distribution (Smetacek et al, ).…”
Section: Biology I: Phytoplankton Of the Wgmentioning
confidence: 99%
“…In Antarctic coastal zones, turbidity affects mesozooplanktonic organisms, such as euphausiids and copepods, modifying their distribution, decreasing their ingestion rates and feeding capacity [28,58,59] and producing episodes of mortality [26]. On the other hand, several studies in the WAP showed that food supply is among the most important factors controlling the dynamics of microzooplankton assemblages [18,27,60]. This would indicate that, in our study, the effects of environmental variables on micro-and mesozooplankton biomass were indirect and direct, respectively.…”
Section: Zooplankton Succession: Environmental Effects Vs Predator-prmentioning
confidence: 99%
“…The last authors reported the existence of abrupt changes in sea surface temperature and salinity mostly related to climate cycles under the influence of the Southern Annular Mode (SAM) and El Niño Southern Oscillation (ENSO). These drivers influence micro and mesozooplankton assemblage dynamics both directly and indirectly [26][27][28] in PC during summer due to changes in the oceanographic conditions in the water column and the quality of the food available.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors reported lower values of surface temperature in waters near FG than in those bordering Maxwell Bay during summers (e.g. Klöser et al 1994, Garcia et al 2016). Additionally, summer S values in a thin surface layer increase outwards, where the influences of the FG is less important (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, summer S values in a thin surface layer increase outwards, where the influences of the FG is less important (Fig. 4, upper panel; Klöser et al 1994, Garcia et al 2016). However, no significant thermohaline differences are observed between the two regions of inner PC: CA and the region closer to the glacier, NA (Table I).…”
Section: Discussionmentioning
confidence: 99%